1978
DOI: 10.1056/nejm197807132990203
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension Associated with Prekallikrein Activator (Hageman-Factor Fragments) in Plasma Protein Fraction

Abstract: Thirteen lots of plasma protein fraction made by one manufacturer were implicated in 23 recent reports of hypotension in surgical patients. Four of these patients required resuscitation after rapid administration of the product in the postoperative period. All implicated lots had prekallikrein-activator activity but low levels of bradykinin and kallikrein. The prekallikrein activator was identified as Hageman-factor fragments by molecular weight (35,000 as estimated by gel chromatography), isoelectric point (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
1

Year Published

1979
1979
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(65 citation statements)
references
References 15 publications
2
62
0
1
Order By: Relevance
“…The plasma kallikrein-kinin system is believed to be involved in the hypotensive reaction since the preparations are frequently contaminated by bradykinin 26 and by a prekallikrein activator, Hageman factor fragment. 21 Inhibition of CE prolongs the hypotensive effects of kinins and abolishes the vasoconstrictor effect of renin by blocking the release of angiotensin II. 8 '' Bradykinin is inactivated mainly by two enzymes, kininase I and kininase II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma kallikrein-kinin system is believed to be involved in the hypotensive reaction since the preparations are frequently contaminated by bradykinin 26 and by a prekallikrein activator, Hageman factor fragment. 21 Inhibition of CE prolongs the hypotensive effects of kinins and abolishes the vasoconstrictor effect of renin by blocking the release of angiotensin II. 8 '' Bradykinin is inactivated mainly by two enzymes, kininase I and kininase II.…”
Section: Discussionmentioning
confidence: 99%
“…21 - 26 The presence of kinins, prekallikrein activator and kininase II inhibitors may explain the severe hypotension encountered in some cases after infusion of such preparations, especially when the lung is excluded from the circulation, since the pulmonary vascular bed is very active in cleaving kinins." This study of the inhibition of CE by albumin fragments should help to clarify the nature of complexing of the enzyme by albumin and possibly by other plasma proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review has appeared (56) of the early studies documenting changes in the contact system in such disorders as the carcinoid (57), postgastrectomy (58), and nephrotic syndromes (59), as well as in type Ila hyperlipoproteinemia (60) and in transfusion reactions (61). The role of surface-mediated defense reactions can be better illustrated by considering the response ofthis system to the challenge of infection, hyperacute allograft rejection, and allergic reactions.…”
mentioning
confidence: 99%
“…Albumin can occasionally have other poorly characterized harmful effects, such as hypotension, caused by vasoactive peptides (Alving et al, 1978) or it can cause renal damage (Boesken et al, 1977), but these effects are rare. Some have even suggested that the chemical properties of albumin may be helpful, by improving drug handling or by supplying antioxidants (Quinlan, 1998).…”
Section: Can Albumin Transmit Infectious Agents?mentioning
confidence: 99%